Efficacy of vancomycin lock therapy for totally implantable venous access port-related infection due to coagulase-negative staphylococci in 100 patients with cancer. (4th April 2023) - Lafaurie, Matthieu; Montlahuc, Claire; Kerneis, Solen; de Lastours, Victoire; Abgrall, Sophie; Manceron, Véronique; Couzigou, Carine; Chabrol, Amélie; de Raigniac, Axelle; Lescure, Xavier; Longuet, Pascale; Lesprit, Philippe; et al.
Abstract: Objectives: Data on the efficacy of vancomycin catheter lock therapy (VLT) for conservative treatment of totally implantable venous access port-related infections (TIVAP-RI) due to CoNS are scarce. The aim of this study was to evaluate the effectiveness of VLT in the treatment of TIVAP-RI due to CoNS in cancer patients. Methods: This prospective, observational, multicentre study included adults with cancer treated with VLT for a TIVAP-RI due to CoNS. The primary endpoint was the success of VLT, defined as no TIVAP removal nor TIVAP-RI recurrence within 3 months after initiation of VLT. The secondary endpoint was 3 month mortality. Risk factors for VLT failure were also analysed. Results: One hundred patients were included [men 53%, median age 63 years (IQR 53–72)]. Median duration of VLT was 12 days (IQR 9–14). Systemic antibiotic therapy was administered in 87 patients. VLT was successful in 44 patients. TIVAP could be reused after VLT in 51 patients. Recurrence of infection after completion of VLT occurred in 33 patients, among which TIVAP was removed in 27. Intermittent VLT (antibiotic solution left in place in the TIVAP lumen part of the time) was identified as a risk factor for TIVAP-RI recurrence. At 3 months, 26 deaths were reported; 1 (4%) was related to TIVAP-RI. Conclusions: At 3 months, success of VLT for TIVAP-RI due to CoNS was low. However, removing TIVAP was avoided in nearly half the patients. Continuous locks should be preferred to intermittent locks. Identifying factors of success is essential to select patients who may benefit from VLT.